The Effect of Bureaucracy Professionalism on Employee Performance in Regional Income Management Agency Bandung City - Ira Lusiawati (Budapest International Research and Critics University, 2022)
This research stars from the fundamental problems of not yet optimal employee performance at the Regional Revenue Management Agency in the city of Bandung.It is suspected that the problem has not been carried out by Bureaucratic Professionalism on Employee Performance at the Bandung City Regional Revenue Management Agency. This study uses a quantitative approach to determine the relationship between variables in a population through hypothesis testing. The research method used is the Explanatory Survey Method with data collection techniques using a five-scale questionnaire. The number of respondents was 167 people, taken by simple random sampling from a population of 286 people at the Bandung City Regional Revenue Management Agency. The data processing technique uses Structural Equation Modeling (SEM). Based on the results of the research, the exogenous variable, namely the Bureaucratic Professionalism variable on Employee Performance as an endogenous variable, is significant. In detail, the results of this study indicate that: The influence of the Bureaucratic Professionalism variable (X) which consists of: Knowledge Aspects, Skills Aspects, and Obedience Aspects on the Code of Ethics has an effect of 0.33 and a significant 2.78 on Employee Performance (Y). Research findings on the variable of bureaucratic professionalism, namely the Aspect of Honesty and Overall research on the effect of bureaucratic professionalism on employee performance has a positive influence on the regional revenue management agency in the city of Bandung.